IMPLEMENTASI APLIKASI PEMBELAJARAN UNTUK ANAK BERBASIS ANDROID - Sam'ani, Sam'ani; Sutami, Sutami; Qamaruzzaman, Muhammad Haris (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Permendiknas No. 16/2007 concerning Academic Qualification Standards and Teacher Competence, Pedagogical Competence of 5th / Senior High School teachers says that